Upaya Niniak Mamak Dalam Membina Akhlak Kemenakan Di Masa Pandemi Covid-19 Kelurahan Koto Panjang Dalam Kecamatan Lamposi Tigo Nagari Kota Payakumbuh - Fauziatul Husna; Pendi Hasibuan (Program Studi Akuntansi IKOPIN, 2022)
This research is motivated by the existence of the Niniak Mamak phenomenon that has not maximally carried out its duties or the lack of firmness of regulations given to nephews. Or Niniak Mamak thinks that moral inculcation is only a concept that must be understood at school and given by subject teachers at school. Niniak Mamak's efforts in fostering nephew's morals are not given much attention. Their knowledge of morals is lacking, and their nieces and nephews act according to their heart's will, for example, when the Maghrib call to prayer rings, boys sing in the shop who should go to pray Maghrib, nephews gather with the opposite sex until late at night, some nephews also say- dirty words between each other, and also nephews lack respect for older people. To discuss the research results, this research method is used which is field research, (Field research) with a qualitative descriptive approach, in this study the author describes the problems in the field according to the facts that the authors find in the field. In this study, the author describes the work of Niniak Mamak in fostering the morals of his nephew, Koto Panjang Village Dalam, Lamposi Tigo Nagari District, Jota Payakumbih. In collecting data, the writer uses observation and interview techniques with informants related to Niniak Mamak's efforts in fostering the character of his nephew using the Snowball Sampling technique. Techniques of analysis using techniques. From the results of the research that has been done, it can be concluded that Niniak Mamak's efforts in fostering the morals of the nephews of Koto Panjang Village in Lamposi Tigo Nagari District, Payakumbuh City are the efforts of Niniak Mamak in fostering the morals of the nephews, namely Wilayat, Hikayat, Advice, Approaching nephews with reason, giving limit to nephew. And Niniak Mamak's obstacles in fostering niece's morals are time and limited knowledge